Nitrogen Cycling at Cold Climate Mine Sites in Northen Sweden - Nilsson, Lino (Luleå tekniska universitet, Institutionen för samhällsbyggnad och naturresurser, 2016)
High nitrogen discharge from mining sites has been an environmental issue that has been closely studied in the recent years. The environmental effects of high nitrogen discharge are mainly eutrophication, but can also lead to changed species composition and algae blooms. Nitrogen is a highly abundant element and is the most abundant element in the atmosphere, where 78% by volume is present as dinitrogen (N2 ). Nitrogen is present in reduced form in all organic life as ammonium (NH4 + ). Nitrogen is also present in reduced form as nitrate (NO3 - ) or nitrite (NO2 - ) in most aquatic systems. Both nitrate and ammonium is contributing to eutrophication problems worldwide and ammonia (NH3 ) is direct toxic in high concentration to certain sensitive aquatic species. Nitrate in high concentration is also direct toxic, both to humans but also to aquatic biota. To trace and quantify different nitrogen transforming processes, their sources and their sinks is called tracing nitrogen cycling and is important due to the environmental effect of nitrogen. Nitrogen is available in many different species and oxidation states which all have their respective geochemistry. This thesis focuses on tracing the complex nitrogen cycle in two different cold climate mining systems in northern Sweden using two different methods. The two studied systems are: The LKAB underground iron ore mine in Kiruna Boliden Minerals AB open pit copper ore mine Aitik outside Gällivare Two different approaches were used to trace the nitrogen cycling. The LKAB Kiruna mine was investigated using stable nitrogen isotopes. The isotope analysis showed high capability to trace nitrogen cycling, both quantative and qualitative. We also showed the origin of the isotope signals which gives indication to the different sources of nitrogen in the mine. The presented study shows presence of nitrification, ammonium volatilization and ammonium adsorption to waste rock to occur in the water transport system. The nitrogen cycling in the Boliden Aitik mine was investigated ...